(untitled) (Transport systems and technologies, 2020)
The analysis of the technological process of determining the parameters of rolling stock units (using the example of wheel set bandages) has been carried out in the article. It has been determined that its implementation by a person using a contact measuring instrument and manual recording of the results can lead to the appearance of errors in perception, attention, memory and thinking. These human errors can occur throughout the entire technological process.